2023
DOI: 10.1002/elps.202300031
|View full text |Cite
|
Sign up to set email alerts
|

Analytical separation of plasmid DNA isoforms using anion exchanging chromatographic monoliths with 6 µm channels

Nejc Pavlin,
Urh Černigoj,
Mojca Bavčar
et al.

Abstract: High‐performance liquid chromatography (HPLC)‐based analytical assays are used to effectively monitor purity and quantity of plasmid DNA (pDNA) throughout the purification process. However, the phenomenon of physical entrapment of open circular (OC) isoforms pDNA inside narrow channels of chromatographic support decreases its accuracy and precision and the effect increases with pDNA size. The purpose of the study was to develop a chromatographic method for accurate analytical separation between isoforms of <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A part of the published manuscripts was also presented at the last Monolith Summer Symposium that was held last year in Portorož, Slovenia. As a logical consequence of the spirit of this time, the topics of most papers that are summarized here are dealing with purification of nanoparticles like viruses [1][2][3], plasmid DNA isoforms [4,5] and RNA drug substances [6]. As is well known, monolithic stationary phases (including membranes) were firstly developed for fast separation of proteins [7], but only the last manuscript in this issue reports the development of a new monolithic stationary phase for protein separation [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A part of the published manuscripts was also presented at the last Monolith Summer Symposium that was held last year in Portorož, Slovenia. As a logical consequence of the spirit of this time, the topics of most papers that are summarized here are dealing with purification of nanoparticles like viruses [1][2][3], plasmid DNA isoforms [4,5] and RNA drug substances [6]. As is well known, monolithic stationary phases (including membranes) were firstly developed for fast separation of proteins [7], but only the last manuscript in this issue reports the development of a new monolithic stationary phase for protein separation [8].…”
Section: Introductionmentioning
confidence: 99%
“…The next three papers are dedicated to fractionation of materials containing different DNA and RNA forms [4][5][6]. Kralj et al reported the optimization of production of large plasmid DNA isoforms with sizes over 10 kbp using anion exchange monoliths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids pHELP (11.6 kbp, 19% OC, 81% SC), pmFIX6 (6.7 kbp, 1% OC, 7% lin, 82% SC, 10% multimers [MM]; 1.8% gDNA), pGMAAV8_Rep-Cap (7.3 kbp, 7% OC, 1% lin, 92% SC; 0.25% gDNA) and pIVTeGFP (3.3 kbp, 4% OC, 67% SC, 28% MM) were stored in 50 mM TRIS, 10 mM EDTA, 0.75 M NaCl, pH 7.2. Isoform purity for each of the plasmids was determined by CIMac pDNA AEX HPLC analysis as described previously (Pavlin et al, 2023) and the gDNA content was determined with qPCR.…”
mentioning
confidence: 99%
“…Column (6 µm chan-nels) were performed as previously described (Pavlin et al, 2023). Samples were diluted with binding MP used for analysis to reduce AS concentration below 0.5 M (e.g., samples in 1.55 M AS were diluted three times) and to reduce pDNA concentration, ideally to 10 ng/µL (e.g., sample with 90 ng of pDNA/µL was diluted nine times).…”
mentioning
confidence: 99%